Pengembangan Kemampuan Keagamaan Peserta Didik Berbasis pada Kecakapan Dasar Keagamaan (Studi Kebijakan Pemerintah Kota Mojokerto Nomor 23 Tahun 2011 Tentang Sertifikasi Kecakapan Dasar Keagamaan di Sekolah Dasar Negeri Pulorejo 2 Dan Madrasah Ibtidaiyah - Ismail, Ismail (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Mojokerto municipal government issued Mayor regulation No. 23 of 2011 on certification of basic religious proficiency (KDK). With the existence of this Mayor's regulation, her hope in the future so that religious life in Mojokerto city will be more advanced and qualified. The focus of this research are: 1) What components are in Basic Religious Essentials ?, 2) How is the implementation of Mojokerto Mayor's Policies number 23 of 2011 on Certification of Basic Religious Vocabulary ?, 3) How is the uniqueness of developing religious ability of learners based on Basic Religious Essentials ?, 4) How is the model of developing the religious ability of learners based on Basic Religious Abilities ?. This research type is qualitative descriptive, to get data, researcher use method of interview, observation and documentation. The data analysis technique used is the theory presented by Miles and Hubberman that is data reduction, data presentation and conclusion. The results of this study are: 1). Component of KDK refers Mojokerto Mayor Regulation Number 23 of 2011 on the granting of KDK certification for elementary school / Madrasah Ibtidaiyah students; 2). Implementation of the Policy on Basic Religious Abilities through the stages: a). Planning; b). Implementation. c). evaluation. 3). The uniqueness of developing the religious ability of learners based on the basic religious skills are: a). The existence of a new and unique regional regulation unlike in general, b). The existence of the application of KDK certificate as one of the requirements for registration of school examination for 6th grade students of SD / MI. c). The existence of the application of KDK certificate as a condition to enter SMP shade Mojokerto Municipal Government. d). The existence of cooperation between formal education institutions SD / MI with non-formal religious education institute Taman Pendidikan Al Qur'an (TPQ) in evaluation of policy implementation and making of KDK certificate. 4). Model development of religious ability of learners based on Basic Religious Abilities through learning process with exemplary and habituation.